Social responsibility it's my hobby - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1974)
This video involves viewers in a situation that requires them to examine their own sense of social responsibility. What factors would they consider in this situation. How would they face possible ostracism by their peers. How muchthey owe to their fellow human being
Keywords: Responsibility in adolescence -- Adolescence psychology; Social interaction in adolescence